1995
DOI: 10.1111/j.1600-0773.1995.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Inversely Regulates DNA Synthesis and Phosphoenolpyruvate Carboxykinase mRNA Levels in Cultured Rat Hepatocytes: Interactions with Insulin, Glucagon, and Transforming Growth Factor β1.

Abstract: In hepatocytes, glucocorticoids control the expression of several genes and exert significant, but complex, regulation of the proliferation. To shed more light on the growth responses to glucocorticoids in these cells, we treated adult rat hepatocytes in primary culture with dexamethasone, in various combinations with other hormones (insulin, glucagon, transforming growth factor beta 1 (TGF beta 1)), and examined the relationship between the effects on the DNA synthesis and the mRNA level of phosphoenolpyruvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…The effect of insulin on DNA synthesis seems to be dominant by comparison with other hepatic mitogens, such as TGF-␣ and hepatocyte growth factor (22). In adult rat hepatocytes, insulin is also capable of reversing the inhibitory effect of glucagon and glucocorticoids on DNA synthesis (52).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The effect of insulin on DNA synthesis seems to be dominant by comparison with other hepatic mitogens, such as TGF-␣ and hepatocyte growth factor (22). In adult rat hepatocytes, insulin is also capable of reversing the inhibitory effect of glucagon and glucocorticoids on DNA synthesis (52).…”
Section: Discussionmentioning
confidence: 95%
“…We found that DNA synthesis was stimulated by insulin and inhibited by dexamethasone in hepatocytes isolated from control animals. Insulin has been reported to enhance DNA synthesis in both fetal and adult rat hepatocytes (27,40), but the role of glucocorticoids in hepatocyte proliferation is unclear: they have been found to potentiate DNA synthesis in the fetus (40) or inhibit it in the adult (52). The effect of insulin on DNA synthesis seems to be dominant by comparison with other hepatic mitogens, such as TGF-␣ and hepatocyte growth factor (22).…”
Section: Discussionmentioning
confidence: 99%
“…14) Other factors belong to the inhibitors group, as follows: Dex suppresses hepatocyte growth in cultured hepatocytes. [19][20][21] Hepatocytes cultured at high density show lower levels of hepatocyte growth compared with those cultured at low density. 18) Hepatocytes cultured on EHS-Matrigel 22) and PVLA 23) show extremely low levels of hepatocyte growth compared with those cultured on collagen and plastic dishes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hepatocyte growth is regulated in cultured hepatocytes by various other factors including cell density, 18) humoral factors such as dexamethasone (Dex), [19][20][21] hepatocyte growth factor (HGF) and epidermal growth factor (EGF), 14) and cellular substratum such as EHS-Matrigel 22) and lactose-carrying styrene polymer (PVLA). 23) In relation to our report, the question of whether regulation of hepatocyte growth by these factors could be mediated by concurrent change in AnxA3 expression seemed interesting; however, it remained to be elucidated whether these factors cause change in AnxA3 expression.…”
Section: ϩmentioning
confidence: 99%